Chemical Composition of Kickxia aegyptiaca Essential Oil and Its Potential Antioxidant and Antimicrobial Activities - Ahmed M. Abd-ElGawad; Yasser A. El-Amier; Giuliano Bonanomi; Abd El-Nasser G. El Gendy; Abdallah M. Elgorban; Salman F. Alamery; Abdelsamed I. Elshamy (Plants, 2022)
The exploration of new bioactive compounds from natural resources as alternatives to synthetic chemicals has recently attracted the attention of scientists and researchers. To our knowledge, the essential oil (EO) of Kickxia aegyptiaca has not yet been explored. Thus, the present study was designed to explore the EO chemical profile of K. aegyptiaca for the first time, as well as evaluate its antioxidant and antibacterial activities, particularly the extracts of this plant that have been reported to possess various biological activities. The EO was extracted from the aerial parts via hydrodistillation and then characterized by gas chromatography-mass spectrometry (GC-MS). The extracted EO was tested for its antioxidant activity via the reduction in the free radicals, 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). In addition, the EO was tested as an antibacterial mediator against eight Gram-negative and Gram-positive bacterial isolates. Forty-three compounds were identified in the EO of K. aegyptiaca, with a predominance of terpenoids (75.46%). Oxygenated compounds were the main class, with oxygenated sesquiterpenes attaining 40.42% of the EO total mass, while the oxygenated monoterpenes comprised 29.82%. The major compounds were cuminic aldehyde (21.99%), caryophyllene oxide (17.34%), hexahydrofarnesyl acetone (11.74%), ar-turmerone (8.51%), aromadendrene oxide (3.74%), and humulene epoxide (2.70%). According to the IC50 data, the K. aegyptiaca EO revealed considerable antioxidant activity, with IC50 values of 30.48 mg L−1 and 35.01 mg L−1 for DPPH and ABTS, respectively. In addition, the EO of K. aegyptiaca showed more substantial antibacterial activity against Gram-positive bacterial isolates compared to Gram-negative. Based on the minimum inhibitory concentration (MIC), the EO showed the highest activity against Escherichia coli and Bacillus cereus, with an MIC value of 0.031 mg mL−1. The present study showed, for the first time, that the EO of K. aegyptiaca has more oxygenated compounds with substantial antioxidant and antibacterial activities. This activity could be attributed to the effect of the main compounds, either singular or synergistic. Thus, further studies are recommended to characterize the major compounds, either alone or in combination as antioxidants or antimicrobial agents, and evaluate their biosafety.